Ẕaḵẖīrah-yi manāqib : kāmil maʻ Haftband-i Mullā Kāshī - Kāshī, Mullā (Manejar Kutub Ḵẖānah-yi Is̲nāʼ ʻAsharī, 1970)
Poems, by various poets, in praise of ʻAlī, the first Shiite Imam; recited by South Asian Shiite Muslims after their daily prayers to seek his intercession.